The Effect of Diabetic Foot Spa on Neuropathy in Type 2 Diabetes Mellitus Patients - Djafar, Rizkan Halalan; Harun, Nurain; Riu, Silvia Dewi Mayasari (GLOBAL HEALTH SCIENCE GROUP, 2025)
Type 2 diabetes mellitus can cause various complications in sufferers, both acute and chronic. One of the most common chronic complications is peripheral vascular disease and diabetic neuropathy. Diabetic neuropathy is the main complication of diabetes mellitus. When someone already has diabetes mellitus, the thing that can be done is to prevent complications of diabetic neuropathy by improving blood circulation in the feet. This study aims to determine the effect of Foot SPA Diabetic on neuropathy in patients with type 2 diabetes mellitus. This study is a quasi-experimental study with a one group pre-test-post-test approach. This study was conducted once a week for 4 weeks. The sample in this study was 16 respondents using the Purposive sampling technique. The research instruments used were Monofilament tests and observation sheets.The results of the analysis using the Wilcoxon test obtained a significant difference in the sensitivity values of the right and left feet before and after the Diabetic Foot SPA intervention, namely p value = 0.000 (p value <0.05), with an average pre-test value of the right foot 1.88 to 2.81. while the average pre-test value of the left foot 1.69 to 2.81 after the Diabetic Foot SPA intervention. The conclusion of this study concluded that Diabetic Foot Spa which is done for 30 minutes once a week for 4 weeks will increase foot sensitivity in patients with diabetes mellitus.